2015
DOI: 10.1016/j.autneu.2015.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Cybersickness provoked by head-mounted display affects cutaneous vascular tone, heart rate and reaction time

Abstract: Cybersickness provoked by head-mounted display affects cutaneous vascular tone, heart rate and reaction time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 21 publications
4
56
0
Order By: Relevance
“…Together, the increase in sympathetic and the decrease in parasympathetic activities resulted in an increased heart rate in stressful scenarios compared to control scenarios. In [9,14,32], the average heart rate reactivity was 5-8 beats per second; in the study [1], subjects with high subjective estimates of nausea had an increase in heart rate of 13 beats per second. In studies [1,9], an increase in heart rate had positive relationships with nausea, which also had negative relationships with the length of stay in a stressful environment.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Together, the increase in sympathetic and the decrease in parasympathetic activities resulted in an increased heart rate in stressful scenarios compared to control scenarios. In [9,14,32], the average heart rate reactivity was 5-8 beats per second; in the study [1], subjects with high subjective estimates of nausea had an increase in heart rate of 13 beats per second. In studies [1,9], an increase in heart rate had positive relationships with nausea, which also had negative relationships with the length of stay in a stressful environment.…”
mentioning
confidence: 74%
“…A subject's locomotion in a virtual environment evokes a side effect of VIMS, such as drowsiness, dizziness, pallor, cold sweat, oculomotor disturbances, nausea, and (rarely) vomiting [8]. In the virtual Roller Coaster simulation, VIMS scores had a positive correlation with the maximum nausea score during the ride and a negative correlation with the duration of the ride [1,9]. However, the illusory sensations of own body movement (vection) and VIMS are not identical and have a complex indirect connection, because vection may occur without VIMS [10] and vice versa [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Dennison et al measured physiological changes of participants during VR use and found out that changes in breathing, stomach activity, and blinking are related to cybersickness and can be used to predict the severity of it. Nalivaiko et al conducted a study by dividing the sample into two groups based on initial skin temperature and discovered that cybersickness caused an increase in skin temperature for the group with lower initial temperature.…”
Section: Related Workmentioning
confidence: 99%
“…A prevalent alternative to the use of questionnaires is collecting physiological measurements. Skin temperature, heart rate, electrogastrogram, electrocardiogram, electrooculogram, galvanic skin response, photoplethysmogram, and breathing rate have been utilized to estimate cybersickness …”
Section: Introductionmentioning
confidence: 99%